PECULIARITIES OF WORK AND STRESS OF UNIVERSITY TEACHERS - Bulotaitė, Laima; Bliumas, Remigijus; Pociūtė, Birutė (Acta Paedagogica Vilnensia, 2008)
The reform of higher education, that lasts for a long time, as well as changes in universities force university teachers to adapt to new circumstances and demands. The article analyses stress and job attitude of university teachers in Lithuania. 255 teachers of different universities (49 percent male and 51 percent female) have been surveyed. The survey has revealed that during the last few years the work load of university teachers has increased significantly in all kinds of activities (teaching, research, participation in projects, international collaboration, etc.). For this reasons most of university teachers dedicate their free time to work. A significant difference has been estimated between activities, which are considered prior by university teachers and work, which university administration considers as priority. This discrepancy of opinions may be the reason for job disappointment, disagreement with the administration and even disloyalty to the employer. The biggest stressors for university teachers are higher education system, low motivation of students and big work load. Women teachers are more stressed by different work range than men. The investigation revealed that university teachers are quite satisfied with their job. Non of university teachers indicated being highly discontent with their job, while 15,2 percents stated, that they are very satisfied with their job at the university. The research has detected, that older teachers and those, who work at the university for a longer time, are more satisfied with their jobs than the younger and less experienced colleagues. It was ascertained, that the more stress is felt, the less job satisfaction is experienced.
Keywords: pecularities of Work; stress; university Teachers; stressors; satisfaction of work